2018
DOI: 10.1002/sd.1899
|View full text |Cite
|
Sign up to set email alerts
|

Poverty alleviation among persons with disabilities via United Nations' sustainable development goals in Ghana: Voices of stakeholders with disabilities

Abstract: Consistently, it has been reported that persons with disabilities face multiple challenges in societies and thus it is important that deliberate intervention programs are initiated to empower them to overcome exclusion. The United Nations has taken the lead through the Sustainable Development Goals (SDGs) project, which is a framework for assisting countries and donors in their efforts to alleviate poverty. This article documented the experiences of persons with disabilities with respect to global efforts towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…There is a global agenda towards eradicating extreme poverty by 2030. Because persons with disabilities are usually poor and dependent in societies such as Ghana (Anthony, ; Opoku et al, ), it has been suggested that governments should devise means to integrate them in economic activities. It is against this backdrop that we explored the perceptions of persons with disabilities regarding their participation in farming.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a global agenda towards eradicating extreme poverty by 2030. Because persons with disabilities are usually poor and dependent in societies such as Ghana (Anthony, ; Opoku et al, ), it has been suggested that governments should devise means to integrate them in economic activities. It is against this backdrop that we explored the perceptions of persons with disabilities regarding their participation in farming.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a Chinese study, Kam and Siu () reported a decrease in depression and anxiety among persons with disabilities who participated in a horticulture programme. In the Ghanaian context, therefore, where persons with disabilities face constant abuse (Kassah et al, ; Opoku et al, ), their involvement in farming could perhaps take their minds off institutional, environmental, and attitudinal forms of discrimination. However, there has been no detailed exploration of the potential of and extent to which persons with disabilities are involved in agriculture in Ghana.…”
Section: Persons With Disabilities and Their Participation In Agriculmentioning
confidence: 99%
See 2 more Smart Citations
“…This population is described as the poorest of the poor in the Ghanaian society. Similarly, they are ranked low in every economic indicator in the country, particularly, access to education for children with disabilities (21,(33)(34)(35)(36).…”
mentioning
confidence: 99%